EMPLOYEE PERFORMACE AFFECTED BY COMPENSATION AND COMPETENCE IN PT COCA COLA AMATIL INDONESIA - Yulius, Yosandi (Dinasti Publisher, 2022)
The purpose of this study was to determine and analyze: (1) Compensation (2) Competence; (3) Employee Performance and (3) Effect of Compensation and Competence on employee performance in the Marketing Division of PT Coca Cola Amatil Indonesia, either simultaneously or partially. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this study is the employee in the Marketing Division of PT Coca Cola Amatil Indonesia with a sample of 50 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the results of the study, it was found that the compensation received by employees at the Marketing Division of PT Coca Cola Amatil Indonesia in general was relatively adequate, the Competence of the Marketing Division employees of PT Coca Cola Amatil Indonesia was appropriate and sufficient to meet the needs, Employee Performance in the Marketing Division of PT Coca Cola Amatil Indonesia is high, and compensation and competence simultaneously affect employee performance in the marketing division of PT Coca Cola Amatil Indonesia. However, partially, compensation is more dominant in influencing employee performance than competence. Because compensation dominantly affects performance, it becomes the first priority in improving employee performance. Therefore, it is recommended that the Marketing Division of PT Coca Cola Amatil Indonesia be given compensation in accordance with the provisions by increasing other benefits, so that they are able to work more professionally.